Rock point load test (PLT index) and its correlation with rock coring rate of bored pile machine - Yusof, Z.M.; Farn, W.S.; Leow, C.S.; Lee, J.C. (Elsevier, 2023)
Rock socketed cast in-situ bored pile has getting more common in the local foundation industry due to high load carrying capacity to support the increasingly large superstructure load. The estimation of bored pile production rate based on rock strength is vital for piling contractor in terms of project planning, site work done forecasting and management of resources. Uniaxial compressive strength (UCS) of rocks is a useful parameter needed for analytical and designing purpose for rock structure, as well as classification of rock strength. Owing to the timeconsuming, tedious and expensive testing procedure of UCS, point load test (PLT) on irregular lump samples has appeared to be the best alternative test to ascertain rock strength, which can be performed on-site or off-site. This research was conducted to establish the correlation between rock PLT index and rock coring rate of bored pile machine, where the PLT results and rock coring data were collected from manual recording at respective project site. Graphical relationship was derived for PLT index against rock coring rate for several pile size categories. As rock UCS is typically adopted for foundation design purpose, the conversion factor between PLT index and UCS was derived for the typical bedrock formation encountered in Kuala Lumpur, namely Granitic rock and Limestone. This study also depicts the estimation of mobilized rock unit shaft friction with respect to the corresponding UCS value, using a recommended empirical formula. From this research study, it was justified that PLT could serve as a cost-effective and straightforward field test which provides invaluable guidance for piling production rate estimation as well as better engineering judgement in foundation design